Degradable polyanhydride networks derived from itaconic acid. Issue 4 (4th January 2021) - Sajjad, Hussnain; Lillie, Leon M.; Lau, C. Maggie; Ellison, Christopher J.; Tolman, William B.; Reineke, Theresa M.
Abstract : Tunable and degradable crosslinked-polyanhydride networks from renewably derived itaconic anhydrides and multifunctional thiols have been developed. Abstract : The development of tunable and degradable crosslinked-polyanhydride networks from renewably derived itaconic anhydrides and multifunctional thiols is presented. Itaconic acid was initially converted to ethyl itaconic anhydride and isoamyl itaconic anhydride via a two-step synthetic procedure on hundred-gram scale with minimal purification. Dinorbornene-functionalized derivatives were prepared via cycloaddition chemistry, and photoinitiated thiol–ene polymerization reactions were explored using commercially available tetra- and hexa-functional thiols, all using solvent-free syntheses. The thiol–ene reaction kinetics of different monomer compositions were characterized by real-time Fourier transform infrared (RT-FTIR) spectroscopy, with the norbornene functionalized derivatives exhibiting the highest reactivity towards thiol–ene photopolymerizations. The thermal and mechanical characteristics of the thermosets were analyzed and the viscoelastic behavior was investigated by dynamic mechanical analysis to understand the influence of the ester functionality and choice of crosslinker on the material properties. The anhydride backbone was found to be susceptible to controlled degradation under physiologically-(phosphate-buffered saline) and environmentally-relevant (artificial seawater) testing conditions over a period of 60 days at 50 °C. This work demonstrates that itaconic acid may be a useful feedstock in the generation of degradable polyanhydride networks via thiol–ene photopolymerization.